ANALISIS PENGEMBANGAN KARIR DAN KOMITMEN ORGANISASI TERHADAP KINERJA KARYAWAN - Hardjokusumo, Heri Sukamto; Chusnah, Chusnah; Devi, Febriyanti Monica (Kinerja, 2021)
This study aims to determine the effect of Career Development and Organizational Commitment on Employee Performance at PT. Bank Tabungan Negara (PERSERO) Tbk. Bekasi Sharia Branch Office. This research was conducted on employees of Bank BTN Syariah Bekasi, the sample in this study amounted to 67 people using a saturated sampling technique (non-probability sampling). The data analysis methods used in this research are validity test, reliability test, classical assumption test, regression analysis, correlation analysis, coefficient of determination, t test and f test using SPSS 25 program. Based on the results of data analysis and hypothesis testing that has been done, it shows that partially Career Development variable (X1) has a positive and significant effect on Employee Performance (Y) with a sig value of 0,000 < 0,05 and t count 4,748 > t table 1,999. While the variable Organizational Commitment (X2) has a positive and significant effect on Employee Performance (Y) with a sig value of 0,000 < 0,05 and t count 4,520 > t table 1,999. The results of the coefficient of determination test (R2) of 0,553, this indicates that the variables of Career Development and Organizational Commitment have an influence on Employee Performance of 55,3% while the remaining 44,7% is influenced by other variables not used in this study.